Evaluación del efecto de ozono (O3) en el control de gorgojo (Acanthoscelides obtectus), en granos almacenados de fréjol (Phaseolus vulgaris L.) en el campus Salache, Cotopaxi. 2021-2022. - Tonato Guanotasig, Monica Paola (2022)
At following work, ozone effect (O3) on Weevil Acanthoscelides obtectus control was evaluated in stored Beans (Phaseolus vulgaris L.). To reduce economic losses caused by this plague, small and medium bean producers resort to the use of chemical products based on Aluminum Phosphide, which leaves phosphine residues causing damage to human and animal health. Primary objective of this research was to evaluate mortality of Acanthoscelides obtectus, and germination percentage of bean seeds exposed on different times. The research work was carried out at "Granos Andinos" laboratory at Technical University of Cotopaxi. A (DBCA) was applied, with factorial arrangement AxB+C using three repetitions, where factor (A) indicates pest development condition (500 g of beans and without beans), factor (B) showed exposure times to ozone, plus a relative control (Aluminum Phosphide) and an absolute control. 15 insects were placed for each treatment and ozone was applied with a concentration of 0.16mg/L, for 40, 50, 60 minutes. Variables under study were mortality of weevil after 72 hours and beans germination after 7 days to finish treatments; these variables were analyzed on InfoStat program, after to obtain statistically significant results on ADEVA, Tukey test was applied at 5% for range comparison. In factor (A), the mortality percentages (100%) were for those weevils (without beans) and for those with 500 g of beans (60%). In factor (B), the highest mortality was (80%) at 60 minutes and the lowest at 40 minutes (57.78%). The AxB interaction presented (100 %) mortality for insects without Beans T4 (40 min), T5 (50 min) and T6 (60 min); compared to those found with T3 beans (60 min) obtained the highest number of dead insects (60 %). Ozone did not cause effects on germination percentage of bean seeds, T1 (40 minutes), T3 (50 minutes), T7 relative control (Aluminum Phosphide), germination percentages were same (53.85%) and in the absolute control T8, higher germination was obtained (58.87%). Ozone can be used as an insecticide to control Acanthoscelides obtectus; therefore, it can be used on management of this pest in beans stored grains.